Using Components to Provide a Long-Term Solution for Repairing Dam Construction Defects - Bhuiyan, Md Ratan; Mia, Md Rezars; Rajun, Md Abdur Rahim; Kumar, Kishor (Transactions on Engineering and Computing Sciences, 2025)
The dam repair process entails the usage of several vital equipment and techniques. There are many problems that dam structures can encounter. Hence, repair is necessary. The paper looks into how different materials and substances are utilized in fixing processes by examining scientific literature and real-world examples. The main aim of this research is to understand how these parts work together to maintain the integrity and functionality of dams and also prolong their lifespan and safety. The study of the properties of materials and their practical applications is vital in the field of dam engineering and maintenance. The data presented here can aid in enhancing methods of construction and maintenance of dams.